HAK PATEN MEREK SEBAGAI PERLINDUNGAN HUKUM DAN KEBERLANJUTAN BISNIS UMKM DI BREBES DALAM BERSAING - Silvana Syah; Eric Hermawan; Amelia Sholeha; Hendri Sucipto; Agung Dharmawan Buchdadi (MUHKAL, 2023)
Brebes Regency is the largest producer of these commodities at the national level. Brebes has a lot of natural wealth potential to be made into local superior products. Brebes' superior products include shallots, salted eggs, salem batik, ornamental ceramics, and tambourines. Another superior product of Brebes is salted eggs which are the result of processed ducks whose popularity is due to their deliciousness and well-known quality and are undoubtedly different from other regions. Brebes has Batik with superior quality under the name Batik Salem. The demand for Brebes superior products, both locally and even imported, continues to increase. The results of the survey and observations are continued with socialization on how to register product patents so that it is hoped that MSME players will be more confident in their business competition so that they are able to have a competitive advantage and business sustainability in the long term.